Challenges in the Peer-review process - Udgam Mishra (Journal of Indonesian Management, 2025)
The peer-review process, considered as the backbone of academic publishing, faces many challenges that undermine its reliability and effectiveness. These issues affect the accuracy of published research and contribute to frustration among authors and reviewers. This study delves into these challenges through qualitative interviews with 10 academic stakeholders, including researchers, reviewers, editors, and the editor-in-chief. The primary focus of the research is to uncover the key issues impacting the peer-review system and to propose practical solutions for addressing them. Using thematic analysis, the study identifies several persistent issues, including the overwhelming workload faced by reviewers, delays in providing feedback, and the influence of personal biases on review outcomes. These factors lead to inconsistent and sometimes unreliable evaluations of research, which can hinder the publication process. Moreover, the lack of standardised review criteria further exacerbates the situation, with different reviewers applying varying standards to the same manuscript. Such inconsistencies compromise the quality and speed of the review process, resulting in significant challenges for both authors and reviewers. The paper proposes several solutions to improve the peer-review system in light of these findings. By addressing these issues, the study contributes to ongoing efforts to enhance the effectiveness of the peer-review system and ensure its continued relevance in the rapidly evolving landscape of academic publishing.